2014
DOI: 10.21273/hortsci.49.11.1444
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses of Zoysia spp. under Tree Shade in the Midwestern United States

Abstract: ‘Meyer’ zoysiagrass (Zoysia japonica Steudel) is commonly planted on home lawns and golf courses in the transition zone; however, poor shade tolerance limits its widespread use. This study was conducted to determine changes and differences in growth among selected Zoysia cultivars and progeny under a natural shade environment over a 3-year period in the transition zone. The study was initiated in June 2010 at the Rocky Ford Turfgrass Research Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…To improve the shade tolerance of turfgrass, shade tolerance of several turfgrass germplasm were identified. The bermudagrass genotypes of WIN10F and STIL03 [184], [(Z. japonica × Z. pacifica)] × Z. japonica progeny of zoysiagrass [185], genotype of NE3490 of buffalograss [186] showed relatively high shade stress tolerance. Additionally, it was reported that zoysiagrass cultivars of 'BA-189', 'Shadow Turf' and 'Empire' had faster establishment under shade stress [181].…”
Section: Shade Stressmentioning
confidence: 99%
“…To improve the shade tolerance of turfgrass, shade tolerance of several turfgrass germplasm were identified. The bermudagrass genotypes of WIN10F and STIL03 [184], [(Z. japonica × Z. pacifica)] × Z. japonica progeny of zoysiagrass [185], genotype of NE3490 of buffalograss [186] showed relatively high shade stress tolerance. Additionally, it was reported that zoysiagrass cultivars of 'BA-189', 'Shadow Turf' and 'Empire' had faster establishment under shade stress [181].…”
Section: Shade Stressmentioning
confidence: 99%
“…In both experiments, Meyer had the poorest performance in Texas shade. Even in the transition zone, Meyer zoysiagrass, along with other cold hardy genotypes such as Chinese Common, exhibited poor performance in natural shade (Peterson et al, 2014). Trappe et al (2011d) also reported that Cavalier, Diamond, El Toro, Palisades, and Zorro all performed well in 50% shade, Meyer performed fair, and ‘Zenith’ performed poorly.…”
Section: Utilizationmentioning
confidence: 99%
“…The results showed that sequencing quality was sufficiently high for downstream analyses. 1 The Min length means the minimum length of transcripts or unigenes. 2 The Max length means the maximum length of transcripts and unigenes 3 The N50 value is defined as the contig length where half of the assembly is represented by contigs of this size or longer.…”
Section: Characteristics Of Genes In Response To Dark-induced Leaf Sementioning
confidence: 99%
“…However, light deprivation caused by the forests exerts many negative effects on the turfgrass. When turfgrass is exposed to light-deficiency conditions, a series of morphological changes happen, including an increase in shoot elongation, leaf length, and leaf area [1][2][3]. Leaf senescence will be induced by prolonged and severe light deficiency.…”
Section: Introductionmentioning
confidence: 99%